Atomically dispersed Ni–Ru–P interface sites for high-efficiency pH-universal electrocatalysis of hydrogen evolution. (February 2021) - Wu, Konglin; Sun, Kaian; Liu, Shoujie; Cheong, Weng-Chon; Chen, Zheng; Zhang, Chao; Pan, Yuan; Cheng, Yuansheng; Zhuang, Zewen; Wei, Xianwen; Wang, Yu; Zheng, Lirong; et al.
Abstract: Designing catalysts with specific active sites is a crucial yet challenging task for high-efficiency electrocatalysis of hydrogen evolution reaction (HER). In this paper, we report the construction of atomically dispersed Ni–Ru–P interface sites (ISs) on Ru single-atomic sites doped nickel phosphide nanoparticles (Ru SAs–Ni2 P NPs) with high-efficiency HER performances in a wide pH range. Especially, the as-constructed atomically dispersed Ni–Ru–P ISs on 2.20 wt% Ru SAs–Ni2 P showed a highly active for catalyzing HER with high turnover frequencies at low overpotential, featuring a high mass activity as well as a superior stability under alkaline conditions. Based on the operando X-ray absorption spectroscopy experiments indicated that the Ni–Ru–P ISs plays an active role in the process of HER and participates in the catalytic process. Density functional theory calculations exhibited that the strong interaction in the atomically dispersed Ni–Ru–P ISs results in an optimized the hydrogen adsorption energy and an elevated hydroxyl adsorption energy, both of which help improve the HER performances. Notably, this work provides a new perspective for the design of high-efficiency HER electrocatalysts by constructing atomically dispersed ISs. Graphical abstract: In this paper, the atomically dispersed Ni–Ru–P interface sites (ISs) on Ru single-atomic sites doped nickel phosphide (Ru SAs–Ni2 P) are successfully constructed, which display high-efficiency HER performances in a wide pH range. Especially, the as-constructed atomically dispersed Ni–Ru–P ISs on 2.20 wt% Ru SAs–Ni2 P show highly active for catalyzing HER under alkaline conditions. The operando X-ray absorption spectroscopy experiments and density functional theory calculations indicate that the Ni–Ru–P ISs plays an active role in the process of HER and participates in the catalytic process. Thereby, this work provides a new perspective for the design of high-efficiency HER electrocatalysts by constructing atomically dispersed ISs. ga1 Highlights: Ru single-atomic sites doped nickel phosphide (Ru SAs–Ni2 P) catalysts are prepared. Atomically dispersed Ni–Ru–P interfacial sites (ISs) are constructed in Ru SAs–Ni2 P. Ni–Ru–P ISs can be used as high-efficiency pH-universal electrocatalysts for HER. Operando XAS experiments reveal that the Ni–Ru–P ISs plays an active role for HER. DFT indicate that Ni–Ru–P ISs are favorable for adsorption of H + and H2 O molecules.